Hydration properties of Portland cement-copper tailing powder composite binder. (10th August 2020) - Liu, Shuhua; Wang, Lu; Li, Qiaoling; Song, Junwei
Highlights: Copper tailing powder as an mineral admixture with maximum content 45% is studied. Copper tailing content higher than 30% has a far greater impact on later hydration. The incorporation of copper tailing powder can reduce compressive strength and change binder's pore structure. The hydrates, morphology and Ca/Si ratio of C-S-H gel have been studied. Abstract: Copper tailing powder with different grinding time and different replacement ratio for cement was used as alternative mineral admixture in Portland cement-copper tailing powder composite binder. The results show that the compressive strength reduces with the increasing content and grinding time of copper tailing powder. Copper tailing powder content, especially higher than 30%, has a far greater impact on later hydration age than early age, which is beneficial for compressive strength development at later hydration stage. The end time of induction period of most mixtures prolongs after the incorporation of copper tailing powder and also shortens with increasing grinding time and the content. With the increase of copper tailing powder content, the most probable pore size increases, and the number of innocuous pores and less harmful pores decrease. The main hydrates of the binders are C-S-H gel, Ca(OH)2, ettringite, CaCO3 and a small amount of dolomite. The Ca(OH)2 content of most mixtures decreases compared with pure cement and also decreases with the increasing content of copper tailing powder, especially for the content higher than 30%. Ca/Si ratio of C-S-H gel is high because of the dissolution rate of Ca 2+ at early age and decreases due to the reaction between superfluous SiO2 in copper tailing powder and high Ca/Si ratio C-S-H gel at later hydration period.